Precision Medicine in Cancers and Non-Communicable Diseases 2018
DOI: 10.1201/9781315154749-17
|View full text |Cite
|
Sign up to set email alerts
|

Customized DNA–directed precision nutrition to balance the brain reward circuitry and reduce addictive behaviors

Abstract: DNA Customization of nutraceutical products is here. In the truest sense, “Gene Guided Precision Nutrition™” and KB220 variants (a complex mixture of amino–acids, trace metals, and herbals) are the pioneers and standard-bearers for a state of the art DNA customization. Findings by both, Kenneth Blum, Ph.D. and Ernest Noble, Ph.D. concerning the role of genes in shaping cravings and pleasure- seeking, opened the doors to comprehension of how genetics control our actions and effect our mental and physical health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 46 publications
(51 reference statements)
0
15
0
1
Order By: Relevance
“…It is strategic to cautiously accept that obtaining better treatment results may stem from identifying reward circuitry gene polymorphisms linked to dopaminergic pathways and opioid receptors. Understanding the relationship between reward circuitry participation in chronic opioid outcomes and corresponding genotypes provides an innovative model to improve opioid replacement therapy and enhance a patient's clinical experience [42], as suggested previously. Importantly, work from Gardner's group [43] at NIDA showed that by using dopamine D3 receptor-knock-out (D3-KO) mice, low D3R availability in the brain represents a risk factor for the Fig.…”
Section: Discussionmentioning
confidence: 98%
“…It is strategic to cautiously accept that obtaining better treatment results may stem from identifying reward circuitry gene polymorphisms linked to dopaminergic pathways and opioid receptors. Understanding the relationship between reward circuitry participation in chronic opioid outcomes and corresponding genotypes provides an innovative model to improve opioid replacement therapy and enhance a patient's clinical experience [42], as suggested previously. Importantly, work from Gardner's group [43] at NIDA showed that by using dopamine D3 receptor-knock-out (D3-KO) mice, low D3R availability in the brain represents a risk factor for the Fig.…”
Section: Discussionmentioning
confidence: 98%
“…RDSS include methods for achieving dopamine homeostasis [22]. RDSS also offers viable application for rejuvenating a brain damaged by toxicity, in neuro-nutrient supplements [23] which provide the amino acid building blocks for proper brain function, and pro-dopamine regulator therapy [24] to combat SUD. After identifying these individuals, and their RDS phenotype, special RDS and RDSS psychoeducation can be provided, as well as tailored individual treatment recovery plans for Reward Deficiency Syndrome [12], to help achieve dopamine homeostasis, within the typical traditional "Treatment as Usual" (TAU), 12 step oriented treatment facility program [25].…”
Section: Discussion Of Reward Deficiency System Solutionsmentioning
confidence: 99%
“…[28], Transcranial Magnetic Stimulation (TMS) [29], and the taking of nutritional supplements designed to repair, restore and regenerate the addiction depleted, RDS challenged brain [23].…”
Section: Reward Deficiency Syndrome Solution Focused Brief Therapy Tomentioning
confidence: 99%
“…The development of a polymorphic gene panel has enabled customized (personalized) anti-obesity compounds and now could provide customized induction of “ dopamine homeostasis ” across many RDS behaviors [39]. This serves as the basis of personalized addiction management utilizing the patented Genetic Addiction Risk Score (GARS™) along with a matched neuro-nutrient known as KB220PAM.…”
Section: Discussionmentioning
confidence: 99%